Adenosine 2A receptors modulate reward behaviours for methamphetamine. (22nd January 2015) - Chesworth, Rose; Brown, Robyn M.; Kim, Jee Hyun; Ledent, Catherine; Lawrence, Andrew J.
Abstract: Addiction to methamphetamine (METH) is a global health problem for which there are no approved pharmacotherapies. The adenosine 2A (A2 A ) receptor presents a potential therapeutic target for METH abuse due to its modulatory effects on striatal dopamine and glutamate transmission. Notably, A2 A receptor signalling has been implicated in the rewarding effects of alcohol, cocaine and opiates; yet, the role of this receptor in METH consumption and seeking is essentially unknown. Therefore, the current study used A2 A knockout (KO) mice to assess the role of A2 A in behaviours relevant to METH addiction. METH conditioned place preference was absent in A2 A KO mice compared with wild‐type (WT) littermates. Repeated METH treatment produced locomotor sensitization in both genotypes; however, sensitization was attenuated in A2 A KO mice in a dose‐related manner. METH intravenous self‐administration was intact in A2 A KO mice over a range of doses and schedules of reinforcement. However, the motivation to self‐administer was reduced in A2 A KO mice. Regression analysis further supported the observation that the motivation to self‐administer METH was reduced in A2 A KO mice even when self‐administration was similar to WT mice. Sucrose self‐administration was also reduced in A2 A KO mice but only at higher schedules of reinforcement. Collectively, these data suggest that A2 A signalling is critically required to integrate rewarding and motivational properties of both METH and natural rewards. Abstract : Methamphetamine (METH) conditioned place preference was absent in adenosine A2A KO mice compared to wildtype littermates (WT). Intravenous self‐administration of METH was intact in A2A KO mice; however, the motivation to self‐administer was reduced in A2A KO mice compared to WT. Sucrose self‐administration was also reduced in A2A KO mice, but only at higher schedules of reinforcement. These data suggest A2A signalling is critically required to integrate rewarding and motivational strength of drug and natural rewards.